THE ROLE OF COLLABORATIVE LEARNING MODELS IN ENHANCING ELEMENTARY SCHOOL STUDENTS’ CRITICAL THINKING SKILLS WITHIN THE MERDEKA CURRICULUM - Ngesti Wahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Critical thinking skills are one of the key competencies emphasized in the Merdeka Curriculum to develop Profil Pelajar Pancasila, students who are independent, reflective, and capable of collaborative problem-solving. However, classroom practices in Indonesian primary schools are still largely dominated by teacher-centered approaches, leaving limited space for students to exercise critical thinking. This study aims to describe the role of collaborative learning models in developing the critical thinking abilities of primary school students within the implementation of the Merdeka Curriculum. A descriptive qualitative approach was employed in a public elementary school in Indonesia. Data were collected through participant observations, in-depth interviews with teachers and students, and document analysis of lesson plans and students’ learning outcomes. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing/verification. The findings reveal that the implementation of collaborative learning models such as group discussions and the Think-Pair-Share strategy, played an important role in fostering active learning interactions, encouraging students to express their opinions confidently, and enhancing their critical thinking skills through activities of interpretation, analysis, and evaluation. These results highlight the essential role of teachers as facilitators in systematically managing collaborative learning processes in alignment with the principles of the Merdeka Curriculum.